OPTOELECTRONIC DEVICE FOR MEASURING THE POWER OF LASER RADIATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A device for measuring the power of the laser radiation.has been designed. The device consists of transmitter and receiving part. The transmitter includes optical radiation source and optical system for collimation of radiation. The receiver part consists of silicon photodiodes, electronic signal processing unit   and  unit for measurements.